CAG-MoE: Multimodal Emotion Recognition with Cross-Attention Gated Mixture of Experts - Axel Gedeon Mengara Mengara; Yeon-kug Moon (Mathematics, 2025)
Multimodal emotion recognition faces substantial challenges due to the inherent heterogeneity of data sources, each with its own temporal resolution, noise characteristics, and potential for incompleteness. For example, physiological signals, audio features, and textual data capture complementary yet distinct aspects of emotion, requiring specialized processing to extract meaningful cues. These challenges include aligning disparate modalities, handling varying levels of noise and missing data, and effectively fusing features without diluting critical contextual information. In this work, we propose a novel Mixture of Experts (MoE) framework that addresses these challenges by integrating specialized transformer-based sub-expert networks, a dynamic gating mechanism with sparse Top-k activation, and a cross-modal attention module. Each modality is processed by multiple dedicated sub-experts designed to capture intricate temporal and contextual patterns, while the dynamic gating network selectively weights the contributions of the most relevant experts. Our cross-modal attention module further enhances the integration by facilitating precise exchange of information among modalities, thereby reinforcing robustness in the presence of noisy or incomplete data. Additionally, an auxiliary diversity loss encourages expert specialization, ensuring the fused representation remains highly discriminative. Extensive theoretical analysis and rigorous experiments on benchmark datasets—the Korean Emotion Multimodal Database (KEMDy20) and the ASCERTAIN dataset—demonstrate that our approach significantly outperforms state-of-the-art methods in emotion recognition, setting new performance baselines in affective computing.